﻿The effect of the composition of Soderm®-Forte gel and the new injectable form of Rexod® on pathology findings in gingival tissue in experimental periodontitis in rats - Pavel A. Galenko-Yaroshevsky; Valeriy K. Leontev; Aleksandr A. Slavinskiy; Kristina V. Tseluiko; Mark A. Zadorozhniy; Sergey S. Todorov; Viktor L. Popkov; Svetlana A. Lebedeva; Anait V. Zelenskaya; Andrey V. Zadorozhniy; Aleksandr A. Verevkin (Belgorod National Research University, 2022)
Introduction: Periodontitis is the most important problem of modern dentistry. The development of new medicines and treatment regimens for patients with periodontal complex lesions is a strategic direction of modern pharmacology and dentistry. In this view, pride of place goes to morphological research, which allows not only to study the effect of drugs on pathomorphological changes in periodontal tissues, but also to estimate their therapeutic effectiveness. Aim of the study: to determine the nature of the effect of the composition of Soderm®-Forte gel and the new injectable form of Rexod® on the pathology findings in gingival tissue of rats with experimental periodontitis. Materials and methods: Experimental periodontitis (EP) was induced in rats by ligature method. The study was performed according to the following algorithm: animals with intact periodontium; animals with untreated EP; animals with EP treated with traditional drug therapy (TDT); animals with EP treated with combinations of TDT with Soderm®-Forte gel and TDT with Soderm®-Forte gel and the new injectable form (NIF) of Rexod®. For pathomorphological examination, biopsy specimen was taken from the gingival margin of the lower incisors. The ImageJ software was used for computer morphometry. Results and discussion: Examination of the gum samples revealed moderate therapeutic effects of the TDT. The combinations of TDT with Soderm®-Forte gel and, to a greater extent, TDT with Soderm®-Forte gel and the NIF of Rexod® showed high pharmacotherapeutic efficacy, manifested in rapid regeneration of the gingival tissues. Conclusion: The combination of TDT, Soderm®-Forte gel and the NIF of Rexod® shows the most beneficial effect on the pathological processes in the gum. The pharmacotherapeutic effect of the studied combination promotes the earliest regeneration of damaged gum tissues and reduces the risk of persistent pathology changes in them.